Green customs and their role in promoting the green economy - Guendouz, Aicha; Alaoui, Safia (Finance and Business Economies Review, 2020)
Green customs is considered a tool for achieving the green economy, as the latter requires the presence of escort services that support environmentally friendly activity; This is what we will address in our study by applying a descriptive and analytical approach in order to know the theoretical framework for green customs And its role in promoting the green economy while highlighting the case of Algeria. And we mentioned the experience of an Arab country. We concluded that green customs is an unopposed initiative in Algeria, and that is, Algeria should seriously consider this issue, which has a major role in supporting the green economy in Algeria.